2021
DOI: 10.14744/felt.2021.00048
|View full text |Cite
|
Sign up to set email alerts
|

Turkish EFL pre-service and in-service teachers’ views on professional development and related activities

Abstract: A large and growing body of literature has investigated the issue of teacher professional development in the EFL context. However, there have been relatively limited studies regarding the comparison of in-service and pre-service teachers' perceptions of professional development. This study, therefore, aims to present inservice and pre-service teachers' perceptions of some professional development activities and to investigate whether differences exist between these two groups regarding their attitudes, beliefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Studies focusing specifically on the use of professional portfolios with in-service and preservice teachers (Hossein, 2021;Evişen, 2021;Haghighi Irani et al, 2020) have found that constructing a professional portfolio and reflecting on one's teaching tend to improve teaching methods. For example, content examination of the participants' portfolios in Doty's study on science teaching revealed a gradual shift from a teacher-centered to a student-centered approach.…”
Section: Portfolio Uses With Pre-service Teachersmentioning
confidence: 99%
“…Studies focusing specifically on the use of professional portfolios with in-service and preservice teachers (Hossein, 2021;Evişen, 2021;Haghighi Irani et al, 2020) have found that constructing a professional portfolio and reflecting on one's teaching tend to improve teaching methods. For example, content examination of the participants' portfolios in Doty's study on science teaching revealed a gradual shift from a teacher-centered to a student-centered approach.…”
Section: Portfolio Uses With Pre-service Teachersmentioning
confidence: 99%
“…This finding is in line with Önalan and Gürsoy (2020) in which the participants had shown moderately high agreement on voluntary participation of in-service training because they thought that training was necessary for teachers' professional development. In another study of Evişen (2021), the in-service teachers stated that professional development was necessary as long as they were doing their job. They described it as an ongoing, lifelong process.…”
Section: Efl Teachers' Attitudes Towards Pdpsmentioning
confidence: 99%
“…These publications, in line with the contemporary global literature, elaborate on the significant use of diverse reflective tools and across different contexts varying from coursework to practicum in EFL teacher education (Bener & Yıldız, 2019;Burhan-Horasanlı & Ortaçtepe, 2016;Dos & Demir, 2013;Genç, 2010;Karakaş & Yükselir, 2021;Kırmızı & Tosuncuoğlu, 2019;Kırmızı & Sarıçoban, 2021;Koçoğlu, 2008;Ögeyik, 2020;Özkan et al, 2014;Yalçın Arslan, 2019;Yeşilbursa, 2011). The body of research also encompasses not only the student teacher reflections but also teacher educators' respective reflective accounts in the given topic (Atay, 2008;Demir, 2015;Evişen, 2021;Sert, 2010).…”
Section: Introductionmentioning
confidence: 99%